Difference in muscle activation patterns during high-speed versus standard-speed yoga: A randomized sequence crossover study. (February 2017) - Potiaumpai, Melanie; Martins, Maria Carolina Massoni; Wong, Claudia; Desai, Trusha; Rodriguez, Roberto; Mooney, Kiersten; Signorile, Joseph F.
Highlights: Significant differences in EMG were seen between the held and transition phases of a pose. High-speed yoga produced overall greater electrical activity than low-speed yoga. High-speed yoga can be used to generate greater muscle utilization. Abstract: Objectives: To compare the difference in muscle activation between high-speed yoga and standard-speed yoga and to compare muscle activation of the transitions between poses and the held phases of a yoga pose. Design: Randomized sequence crossover trial Setting: A laboratory of neuromuscular research and active aging Interventions: Eight minutes of continuous Sun Salutation B was performed, at a high speed versus a standard-speed, separately. Electromyography was used to quantify normalized muscle activation patterns of eight upper and lower body muscles (pectoralis major, medial deltoids, lateral head of the triceps, middle fibers of the trapezius, vastus medialis, medial gastrocnemius, thoracic extensor spinae, and external obliques) during the high-speed and standard-speed yoga protocols. Main Outcome Measures: Difference in normalized muscle activation between high-speed yoga and standard-speed yoga. Results: Normalized muscle activity signals were significantly higher in all eight muscles during the transition phases of poses compared to the held phases (p < 0.01). There was no significant interaction between speed × phase; however, greater normalized muscle activity was seen for highspeed yoga across the entire session. Conclusions: Our results show that transitions from one held phase of a pose to another produces higher normalized muscle activity than the held phases of the poses and that overall activity is greater during highspeed yoga than standard-speed yoga. Therefore, the transition speed and associated number of poses should be considered when targeting specific improvements in performance.